Secondary Atomization of Fuel Oil and Fuel Oil/Water Emulsion through Droplet-Droplet Collisions and Impingement on a Solid Wall - Anastasia Islamova; Pavel Tkachenko; Nikita Shlegel; Genii Kuznetsov (Energies, 2023)
This paper presents findings from an experimental study investigating the secondary atomization of liquid fuel droplets widely used in the heat and power industry exemplified by fuel oil and environmentally promising fuel oil/water emulsion. The scientific novelty comes from the comparative analysis of the critical conditions and integral characteristics of the secondary atomization of the liquid and composite fuels with the greatest potential for power plants. Here, we used two fuel atomization schemes: droplet–droplet collisions in a gas and droplets impinging on a heated solid wall. The temperature of the liquids under study was 80 °C. The velocities before collision ranged from 0.1 m/s to 7 m/s, while the initial droplet sizes varied from 0.3 mm to 2.7 mm. A copper substrate served as a solid wall; its temperature was varied from 20 °C to 300 °C. The main characteristics of droplet interaction were recorded by a high-speed camera. Regime maps were constructed using the experimental findings. It was established that the critical Weber number was several times lower when water and fuel oil droplets collided than during the collision of fuel oil droplets with 10 vol% of water. The secondary atomization of fuel oil/water emulsion droplets by their impingement on a heated solid wall was found to reduce the typical sizes of liquid fragments by a factor of 40–50. As shown in the paper, even highly viscous fuels can be effectively sprayed using primary and secondary droplet atomization schemes. It was established that the optimal temperature of the fuel oil to be supplied to the droplet collision zone is 80 °C, while the optimal substrate temperature for the atomization of fuel oil/water emulsion droplets approximates 300 °C.